Az elmúlt tíz év változásainak vezetői értékelése különböző szervezeti formában működő vállalatoknál - Kerékjártó, Gábor (Acta Agraria Debreceniensis, 2002)
revolutions and changes. Effects of these changes can be sensible at all parts of agricultural production. It results in new ownership and organisation structure. Agriculture has to suit to the new circumstances of changed firm-size and structure. These kinds of changes essentially define conditions of agricultural production in the future, and they have an affect on husbandry of enterprises.To be succeed in managing changes, we have to know the reasons of these alterations and nature of them. It is very important to get to know the advantages and disadvantages of the typical change-management methods and its typology. These methods are more elaborated and widespread at industrial enterprises. It is necessary to get to know the nature, characteristics and reasons of changes, and we should work out ways agricultural companies, taking notice of their speciality.The methods and means of examinationsWe aimed to point out what kind of changing processions were typified the activity of agricultural ventures. What are the speciality, strains, the arousing and obstructive factors of nowadays changes. We made questionnaire and sent them to numerous enterprises.Most of the answers show that leaders are „floating with flow” and most part of their power is used to fight back actually challenges. Generally consciousness is missing, so they are not govern the events still more they are passive objects of occurrence.Naturally, the given answers show, that the most important changes of past are changing of markets, importance of quality production and changes in the structure of enterprises. And – especially at companies, which deal with plant growing –, modifying of structure because of compensation.